Veracity pledge or discreditation strategy? Accusations of legacy disinformation in presidential campaigns in Cabo Verde - Novais, Rui Alexandre (2022)
This study constitutes an original contribution to the understanding of how disinformation gains traction in election campaigning by dwelling on yet to be studied case of the 2016 presidential elections in Cabo Verde. Based upon the results of a qualitative analysis focused on the dynamics of legacy disinformation–that is, false or misleading information diffused by the candidates themselves–across platforms, it concludes that besides not being channel-specific, the incumbency and frontrunner status of one of the candidates can be seen as a specific driver of disinformation used to facilitate the election success.